O-004 Analysis of M2 Occlusions within TREVO Acute Ischemic Stroke (TRACK) stent-retriever Thrombectomy Registry. (29th July 2016) - Castonguay, A; Nogueira, R; English, J; Satti, S; Farid, H; Veznedaroglu, E; Binning, M; Puri, A; Vora, N; Budzik, R; Dabus, G; Linfante, I; et al.
Abstract : Background and purpose: Several recent randomized clinical trials have demonstrated the safety and efficacy of mechanical thrombectomy with stent retrievers for acute ischemic stroke patients with anterior circulation occlusions. However, these trials have limited enrollment of patients with M2 occlusions. Here, we sought to examine the clinical and angiographic outcomes of patients with M2 occlusions in the Trevo Acute Ischemic Stroke (TRACK) stent-retriever thrombectomy multicenter registry. Methods: Data from the investigator-initiated TRACK Registry (631 consecutive AIS patients, 23 clinical centers) was used to examine and compare demographic, clinical, and angiographic outcomes of patients with M1 versus M2 occlusions who were treated with TREVO as first treatment device. Results: Of the 631 patients enrolled in the TRACK registry, 84 (13.3%) had M2 and 344 (54.5%) had M1 occlusions. Mean age was similar between the M1 and M2 cohorts, 66.5 ± 14.4 and 64.7 ± 3.8 years (p = 0.34), respectively. M2 patients had a lower median baseline NIHSS at presentation (14 (IQR 7–9) versus 18(IQR 14–22), p ≤ 0.0001). Time of onset to groin puncture (347 ± 237.4 and 361 ± 232.3, p = 0.63) and total procedural time (85.9 ± 49.9 and 78.3 ± 64.5, p = 0.4) was similar between the M1 and M2 cohorts. The number of passes with TREVO device was greater in the M1 cohort (Median, 2 (IQR 1–3) versus 1(IQR 1–2), p = 0.01) as well as use of rescue therapy (20.2% versus 9.8%, p = 0.03). Patients with M2 occlusions achieved a higher rate of TICI 3 revascularization after the 1 st pass with TREVO device compared to those with M1 occlusions (55.8% versus 40.4%, p = 0.01). There was no significant difference in time to revascularization (78.6 ± 50.7 versus 71.6 ± 45.3, p = 0.2), revascularization success (≥TICI 2 b) (80.5% versus 76.2%, p = 0.4), symptomatic intracranial hemorrhage (5.6% versus 6.0%, p = 0.9), 90 day modified Rankin Scale score 0–2 (51.0% versus 57.4%, p = 0.35), or mortality (16.1% versus 13.2%, p = 0.6) between the M1 and M2 groups, respectively. Conclusions: Patients with M2 Occlusions are more likely to achieve complete recanalization from the first pass with Trevo stent retriever device than M1 occlusion. In addition, the M2 cohort had a numerically higher rate of good clinical outcome and less rate of mortality than M1 group. This substudy is limited by lack of a control M2 group without mechanical thrombectomy. Disclosures: A. Castonguay: None. R. Nogueira: None. J. English: None. S. Satti: None. H. Farid: None. E. Veznedaroglu: None. M. Binning: None. A. Puri: None. N. Vora: None. R. Budzik: None. G. Dabus: None. I. Linfante: None. V. Janardhan: None. A. Alshekhlee: None. M. Abraham: None. R. Edgell: None. M. Taqi: None. R. El Khoury: None. M. Mokin: None. M. Mokin: None. A. Majjhoo: None. M. Kabbani: None. M. Froehler: None. I. Finch: None. S. Ansari: None. R. Novakovic: None. T. Nguyen: None. O. Zaidat: None.